Cholinium Lactate Methacrylate: Ionic Liquid Monomer for Cellulose Composites and Biocompatible Ion Gels. Issue 1 (August 2014) - Isik, Mehmet; Gracia, Raquel; Kollnus, Lessie C.; Tome, Liliana C.; Marrucho, Isabel M.; Mecerreyes, David; Duchet‐Rumeau, Jannick; Gérard, Jean‐François; Galli, Giancarlo
Summary Cholinium, a quaternary ammonium cation, trimethylethanol ammonium, is an essential micronutrient which supports several biological functions. In this work, a new cholinium based ionic liquid methacrylate monomer was used to process cellulose and produce optically transparent coatings through a simple photopolymerization procedure. The same monomer was also employed to manufacture biocompatible ion gels. Simply, the methacrylic monomer was photopolymerized within the ionic liquid matrix to form a gel type material.